Synthesis and in vitro study of 14-aryl-14H-dibenzo[a.j]xanthenes as cytotoxic agents - Bhattacharya, Asish K.; Rana, Kalpeshkumar C.; Mujahid, Mohammad; Sehar, Irum; Saxena, Ajit K. (Bioorganic & Medicinal Chemistry Letters, 2009)
A simple and expedient method for the synthesis of a series of 14-aryl-14H-dibenzo[a.j]xanthenes is described through a one-pot condensation of beta-naphthol with aryl aldehydes catalysed by TaCl(5) under solvent-free conventional heating. The major advantages of the present method are: high yields, less reaction time, solvent-free condition and easy purification of the products. The synthesized 14-aryl-14H-dibenzo[a.j]xanthenes were evaluated against a panel of six human cancer lines of different tissues. Synthesized compound 30 showed IC(50) of 37.9 and 41.3 mu M against Colo-205 and 502713, respectively, whereas 3g showed IC(50) of 41.9 mu M against Colo-205. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Aldehyde; beta-Naphthol; condensation; Cytotoxicity; One-pot reaction; Solvent-free; Tantalum(V) chloride; Xanthenes

Simple and efficient synthesis of 2-Aryl-2,3-dihydroquinolin-4(1H)-ones using silica chloride as a new catalyst under solvent-free conditions - Muthukrishnan, Murugan; Mujahid, Mohammad; Punitharasu, V.; Dnyaneshwar, D. A. (Synthetic Communications, 2010)
A mild, efficient, and high-yielding method for the synthesis of 2-aryl-2,3-dihydroquinolin-4(1H)-ones from their corresponding 2-amino chalcones using silica chloride (SiO2Cl) under solvent-free conditions is described. A series of 2-aryl-2,3-dihydroquinolin-4(1H)-ones containing both electron-donating and electron-withdrawing substituents were synthesized.
Keywords: 2-Amino chalcones; 2-aryl-2; 3-dihydroquinolin-4(1H)-ones; Microwave; silica chloride

Syntheses and biological evaluation of new triazole-spirochromone conjugates as inhibitors of mycobacterium tuberculosis - Muthukrishnan, Murugan; Mujahid, Mohammad; Yogeeswari, P.; Sriram, D. (Tetrahedron Letters, 2011)
A series of novel 1,2,3-triazole fused spirochromone conjugates have been synthesized bearing both spirochromone moiety as well as a 1,2,3-triazole moiety. Some of the compounds have exhibited potential activity against Mycobacterium tuberculosis (virulent strain H37Rv). In particular 5e proved to be the most potent derivative exhibiting MIC = 0.78 mu g/mL. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Antitubercular activity; Click chemistry; Mycobacterium tuberculosis; Spirochromones

Synthesis and antitubercular activity of amino alcohol fused spirochromone conjugates - Mujahid, Mohammad; Gonnade, Rajesh G.; Yogeeswari, P.; Sriram, D.; Muthukrishnan, Murugan (Bioorganic & Medicinal Chemistry Letters, 2013)
A series of 21 new amino alcohol fused spirochromone conjugates have been synthesized, characterized with analytical data and evaluated their antimycobacterial activity against Mycobacterium tuberculosis (virulent strain H37Rv) in vitro. Some of the compounds exerted significant inhibition, in particular, compound 4f found to be the most potent derivative exhibiting MIC = 3.13 mu g/mL. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Amino alcohol; Antitubercular activity; Mycobacterium tuberculosis; Spirochromones

Spirochromone-chalcone conjugates as antitubercular agents: synthesis, bio evaluation and molecular modeling studies - Mujahid, Mohammad; Perumal, Yogeeswari; Sriram, D.; Basavanag, U. M. V.; Dıaz-Cervantes, Erik; Cordoba-Bahena, Luis; Robles, Juvencio; Gonnade, Rajesh Ghanshyam; Karthikeyan, Muthukumarasamy; Vyas, Renu; Krishnan, M. Muthu (RSC Advances, 2015)
A new series of spirochromone annulated chalcone conjugates were synthesized and evaluated for their antitubercular activity against Mycobacterium tuberculosis H37Rv strain. These compounds were subjected to molecular modeling studies using docking and chemoinformatics based approaches. The docking simulations were performed against a range of known receptors for chalcone derived compounds to reveal MTB phosphotyrosine phosphatase B [MtbPtpB] protein as the most probable target based on the high binding affinity scores. Five compounds exhibit significant inhibition, showing minimum inhibitory concentration values i.e. MIC values ranging from 3.13–12.5 μg mL−1. Further analysis of the synthesized compounds with known and in-house developed chemoinformatics tools unequivocally established their potential as anti-tubercular compounds. QSAR modeling revealed a quantitative relationship between biological activities and frontier molecular orbital energies of synthesized compounds. The predictive model can be employed further for virtual screening of new compounds in this series.